Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1089/neu.2014.3361
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Outcome after Traumatic Brain Injury: Development of Prognostic Scores Based on the IMPACT and the APACHE II

Abstract: Prediction models are important tools for heterogeneity adjustment in clinical trials and for the evaluation of quality of delivered care to patients with traumatic brain injury (TBI). We sought to improve the predictive performance of the IMPACT (International Mission for Prognosis and Analysis of Clinical Trials) prognostic model by combining it with the APACHE II (Acute Physiology and Chronic Health Evaluation II) for 6-month outcome prediction in patients with TBI treated in the intensive care unit. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 45 publications
1
18
0
1
Order By: Relevance
“…To adjust for case-mix and injury severity differences between the BAC groups, we used the International Mission for Prognosis and Analysis of Clinical Trials in TBI (IMPACT) prognostic model together with the APACHE II scoring system by using the newly developed IMPACT-APACHE II prediction model. 18 The IMPACT-APACHE II prediction model has shown superior performance in predicting six-month outcome in patients with TBI compared to the individual IMPACT and APACHE II models. 18 We used the IMPACTlab-APACHE II model to achieve best possible case-mix adjustment.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…To adjust for case-mix and injury severity differences between the BAC groups, we used the International Mission for Prognosis and Analysis of Clinical Trials in TBI (IMPACT) prognostic model together with the APACHE II scoring system by using the newly developed IMPACT-APACHE II prediction model. 18 The IMPACT-APACHE II prediction model has shown superior performance in predicting six-month outcome in patients with TBI compared to the individual IMPACT and APACHE II models. 18 We used the IMPACTlab-APACHE II model to achieve best possible case-mix adjustment.…”
Section: Discussionmentioning
confidence: 96%
“…18 The IMPACT-APACHE II prediction model has shown superior performance in predicting six-month outcome in patients with TBI compared to the individual IMPACT and APACHE II models. 18 We used the IMPACTlab-APACHE II model to achieve best possible case-mix adjustment. The IMPACT lab portion of the IMPACTlab-APACHE II prediction model includes several admission characteristics strongly associated with long-term outcome after TBI: age, motor score, pupillary light reaction, Marshall CT score, presence of traumatic subarachnoid hemorrhage, presence of epidural hematoma, hypotensive or hypoxic insults, glucose and hemoglobin concentrations.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Fourth, the FICC does not include data on pupillary reactivity, a prognostic factor that is highly relevant in TBI patients [36]. However, previous studies have shown that a prognostic model based only upon age and GCS is accurate for predicting mortality in TBI patients, even in the absence of pupillary reactivity [20, 37]. Fifth, the FICC database does not include data on overall injury severity measures, such as the injury severity score.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the GiViTI calibration belt was used. Even though the GiViTI belt and H‐L test have been found to generate similar results, the different methods of exploring model performance might have contributed to the different results observed.…”
Section: Discussionmentioning
confidence: 96%